Diagnóstico de un turismo accesible para personas con discapacidades motrices en los establecimientos hoteleros del cantón Quevedo provincia de Los Ríos, año 2018 - Herrera Bajaña, Selena Desireé (2018)
The present investigation was carried out in order to identify the accessibility provided by the hotel establishments, the Quevedo canton, and people with motor disabilities. A direct observation was made of the hotel establishments of the canton. A survey was applied to 100 people with different disabilities, who are in the PAMUNIQ and the Association "SOLIDARIDAD", to determine the accessibility feature that the hotel sector should have to receive tourists with disabilities. According to the surveys it was determined that in this market niche there are no hotels that provide facilities and the highest type of disability is the intellectual, followed by motor disability. Subsequently, an informative manual is produced under regularization and control for tourism included as it is based on the following documents, Ministry of Tourism: Regulation of tourist accommodation, World Tourism Organization: Accessible tourism for all, principles, tools and good practices , Ministry of Tourism: Manual of universal accessibility for the tourist accommodation services sector; divided into five chapters that describe generalities of tourism, accessible tourism, disability, solutions for an accessible hotel design and under what regularization inclusive tourism should be. Services must be improved in society.